Principles of Polymer Chemistry - Ravve, A. (Springer New York : Imprint: Springer, 2012)
This successful textbook undergoes a change of character in the third edition. Where earlier editions covered organic polymer chemistry, the third edition covers both physical and organic chemistry. Thus kinetics and thermodynamics of polymerization reactions are discussed. This textbook also covers such hot topics as photonic polymers, electricity conducting polymers, polymeric materials for immobilization of reagents and drug release, organic solar cells, and organic light emitting diodes. This textbook contains review questions at the end of every chaper, references for further reading, and numerous examples of commerically important processes.